Cognition, conflict, and doctrine: How groupthink fails on a Clausewitz landscape. (April 2020) - Wallace, Rodrick
Real-time conflict takes place on Clausewitz landscapes most notably marked by fog-of-war and frictional limits, uncertainties, and misperceptions. Imposition of such factors on an opponent is, in fact, a standard tactic of confrontation, from courts of law to commerce, from political campaigns to the battlefield. Time-constrained optimization models of institutional effectiveness, based on 'anytime algorithm' methods, suggest that the burden of doctrinal groupthink may become synergistic with fog-of-war and friction to greatly compromise the ability of an institution to respond to shadow price demands imposed by a contending agent or environment. A different, and more direct, approach via a 'simple' stochastic model, provides similar insight.